THE RELATIONSHIP OF SCHOOL PRINCIPAL LEADERSHIP AND WORK MOTIVATION WITH TEACHER PERFORMANCE - Nurhidayati, Nurhidayati; Yarmi, Gusti; Kadarisman, Kadarisman (Universitas Pendidikan Indonesia, 2024)
The purpose of this research is to describe and analyze the relationship between the Leadership of the School Principal and Work Motivation with the Performance of Elementary School Teachers in Mampang Prapatan, South Jakarta, both partially and simultaneously. The research method used in this study is inferential statistical analysis using a quantitative approach with correlation testing. The population in this study consists of all teachers teaching at public elementary schools in Mampang Prapatan, South Jakarta, with purposive sampling techniques used for the sample. The results of this study indicate a significant relationship with a positive and high correlation between the leadership of the school principal and work motivation with the performance of teachers in public elementary schools in Mampang Prapatan, South Jakarta, both partially and simultaneously. The leadership of the school principal is a strong factor that can achieve the school's goals, missions, objectives, and vision, which is carried out through planned, gradual, and sustainable programs. Maintaining and ensuring that teachers receive high motivation is deemed essential for creating quality human resources. The results of this study are expected to provide information to future researchers, especially those related to the leadership of school principals and motivation in relation to teacher performance.